Antioxidant, Antiproliferative, and Antiangiogenesis Effects of Polyphenol-Rich Seaweed (Sargassum muticum). (3rd September 2013) - Namvar, Farideh; Mohamad, Rosfarizan; Baharara, Javad; Zafar-Balanejad, Saeedeh; Fargahi, Fahimeh; Rahman, Heshu Sulaiman
Abstract : In the present study, we evaluated the effect of brown seaweeds Sargassum muticum methanolic extract (SMME), against MCF-7 and MDA-MB-231 breast cancer cell lines proliferation. This algae extract was also evaluated for reducing activity and total polyphenol content. The MTT assay results indicated that the extracts were cytotoxic against breast cancer cell lines in a dose-dependent manner, with IC50 of 22  μ g/ml for MCF-7 and 55  μ g/ml for MDA-MB-231 cell lines. The percentages of apoptotic MCF-7-treated cells increased from 13% to 67% by increasing the concentration of the SMME. The antiproliferative efficacy of this algal extract was positively correlated with the total polyphenol contents, suggesting a causal link related to extract content of phenolic acids. Cell cycle analysis showed a significant increase in the accumulation of SMME-treated cells at sub-G1 phase, indicating the induction of apoptosis by SMME. Further apoptosis induction was confirmed by Hoechst 33342 and AO/PI staining. Also SMME implanted in vivo into fertilized chicken eggs induced dose-related antiangiogenic activity in the chorioallantoic membrane (CAM). Our results imply a new insight on the novel function of Sargassum muticum polyphenol-rich seaweed in cancer research by induction of apoptosis, antioxidant, and antiangiogenesis effects.